Spatiotemporal Evolution and Genesis of the Late Ordovician—Early Silurian Marine Euxinia in Northeastern Upper Yangtze Basin, South China - Wang, Chaoyong; Dong, Zaitian; Fu, Xuehai; Chen, Qing; Liu, Xiaofan; Tang, Mengmeng; Wang, Zetang (Frontiers in Earth Science, 2021)
Marine redox conditions and their dynamic changes were a major factor that controlled the formation of black shale and caused the late Ordovician marine extinction in the Upper Yangtze Basin (South China). However, the spatiotemporal variation and potential controlling factors of marine redox conditions in this area remain unclear. We analyzed whole-rock geochemistry and pyrite sulfur isotopes (δ34Spy) of 47 shale samples from the Late Katian to Rhuddanian in a shelf-to-slope (Qianjiang Shaba section and Wc-1 well) region of northeastern Upper Yangtze Basin, and reconstructed water column redox conditions during the Late Ordovician–Early Silurian Transition. The geochemical characteristics of shale, including the ratio of elements, discriminant function and ternary diagram location in the study area suggest a passive continental margin sedimentary environment, wherein the terrigenous detritus is mainly derived from felsic igneous rocks in the upper crust, showing characteristics of near-source deposition. The redox indices (Fe speciation, Corg/P, UEF, and MoEF) showed that the development of anoxic water, especially euxinia, has obvious spatiotemporal heterogeneity. Under conditions of high availability of active organic carbon and limited sulfate supply, high active Fe input and strong biological irrigation in the shallow water area may effectively remove H2S produced by microbial sulfate reduction, conducive to the prevalence of ferruginous water columns. However, for this deep water area, the rapid accumulation rate of organic matter, decrease in dissolved Fe (caused by upwelling in the open sea), and seawater stratification (caused by the rising of sea level) promoted the development of a euxinic water column. This inference is supported by the covariant relationship between organic carbon accumulation rate, chemical index of alteration, Co × Mn, and δ34Spy. Our study highlights the potential control effects of sea level change, continental weathering and upwelling on the development of euxinic water columns.